Cranial sonographic markers of fetal open spina bifida at 11 to 13 weeks of gestation. (20th December 2019) - Wertaschnigg, Dagmar; Ramkrishna, Jayshree; Ganesan, Sujatha; Tse, Cheryl; Scheier, Matthias; Volpe, Nicola; Ghi, Tullio; Meagher, Simon; Rolnik, Daniel L.
Abstract: Objectives: To compare the sonographic signs of spina bifida obtained on axial and sagittal views of the fetal head between 11 and 13+6 weeks of gestation. Methods: This was a retrospective study including 27 cases of spina bifida and 1003 randomly selected controls. Indirect markers of spina bifida were evaluated on stored ultrasound images. Intracranial translucency (IT), ratio between the brainstem and the brainstem–occipital bone distance (BS/BSOB), and maxillo‐occipital (MO) line were assessed on sagittal view, whereas biparietal diameter (BPD), BPD to abdominal circumference ratio (BPD/AC), and aqueduct to occipital bone (aqueduct of Sylvius [AoS]) distance were measured on the axial plane. Reference ranges were developed, and cases of spina bifida were examined in relation to the reference range. Results: On the sagittal view, detection rates for IT below the fifth percentile, BS/BSOB above the 95th percentile, and an abnormal MO line were 52.3%, 96.3%, and 96.3%, respectively. On the axial view, detection rates for BPD, BPD/AC, and AoS below the fifth percentile were 66.7%, 70.4%, and 77.8%, respectively. Conclusion: The MO line and the BS/BSOB ratio appear to be the best indirect ultrasound markers of spina bifida and can be easily obtained during the routine first‐trimester scan.